How Idealists or how Relativists are Greek Health and Fitness Managers? Assessment of Individual Ethical Ideology by adapting the Ethics Position Questionnaire (EPQ) to a Greek Population - Paschalidou Κατερίνα; Tsitskari Ευστρατία; Alexandris Κωνσταντίνος; Filippou Διονύσιος (Inquiries in Physical Education and Sport, 2022)
Business practice in general, is shaped in respect to the critical decisions of the administrative executives regarding ethics, which are the result of their individual moral ideology. Individual moral ideology is in turn influenced by individual factors such as gender, age, years of experience, education. Business ethics, in the context of the study of the above practices, is related to the evaluation of health & fitness businesses’ ethics which derives from their management and therefore to the managers who are in positions of responsibility, while it has been proven that their ethical values influence the company’s overall culture. The purpose of this research was to test Forsyth’s (1980) Ethics Position Questionnaire (EPQ) for the first time in a Greek population and to check the validity and reliability of the scale. Furthermore, the aim of the research was to assess the individual ethical ideology of fitness business managers (N=249), and to study whether it differs based on their gender, age, years of experience and education. Data were collected through Forsyth’s (1980) Ethics Position Questionnaire (EPQ), assessing through 20 variables how idealistic or relativist a manager is. The questionnaire was translated with the double-direction method and adapted to the Greek population. The results of the present research showed that the specific questionnaire presents moderate to satisfactory internal validity and reliability for the evaluation of the perceived individual ethics of managers. Fitness business managers rate one of the two factors more highly, that of Idealism, while no statistically significant differentiation of managers’ ethical ideology based on their demographics was confirmed, with the exception of their further education. In the health & fitness industry, individual ethics as an evaluation parameter of business ethics can significantly contribute to the understanding of business practices and to the further development of business ethics studies in this field.